Platelet–Eosinophil Interactions As a Potential Therapeutic Target in Allergic Inflammation and Asthma - Shah, Sajeel A.; Page, Clive P.; Pitchford, Simon C. (Frontiers in Medicine, 2017)
The importance of platelet activation during haemostasis is well understood. An understanding of these mechanisms has led to the use of several classes of anti-platelet drugs to inhibit aggregation for the prevention of thrombi during cardiovascular disease. It is now also recognised that platelets can function very differently during inflammation, as part of their role in the innate immune response against pathogens. This dichotomy in platelet function occurs through distinct physiological processes and alternative signalling pathways compared to that of haemostasis (leading to platelet-aggregation), and is manifested as increased rheological interactions with leukocytes, the ability to undergo chemotaxis, communication with antigen presenting cells, and direct anti-pathogen responses. Mounting evidence suggests platelets are also critical in the pathogenesis of allergic diseases such as asthma, where they have been associated with antigen presentation, bronchoconstriction, bronchial hyperresponsiveness, airway inflammation, and airway remodelling in both clinical and experimental studies. In particular, platelets have been reported bound to eosinophils in the blood of patients with asthma and the incidence of these events increases after both spontaneous asthma attacks in a biphasic manner, or after allergen challenge in the clinic. Platelet depletion in animal models of allergic airway inflammation causes a profound reduction in eosinophil recruitment to the lung, suggesting that the association of platelets with eosinophils is indeed an important event during eosinophil activation. Furthermore, in cases of severe asthma, and in animal models of allergic airways inflammation, platelet-eosinophil complexes move into the lung through a platelet P-selectin mediated, eosinophil β1-integrin activation dependent process, whilst platelets increase adherence of eosinophils to the vascular endothelium in vitro, demonstrating a clear interaction between these cell types in allergic inflammatory diseases. This review will explore non-thrombotic platelet activation in the context of allergy and the association of platelets with eosinophils, to reveal how these phenomena may lead to the discovery of novel therapeutic targets.